Pengaruh Konseling Kelompok terhadap Etika Pergaulan - Ma’rufatun Ma’rufatun; Titin Swatinah; Fakhruddin Mutakin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2019)
Today's adolescent social problems are often the topic of conversation and at the same time become a source of concern or concern for parents, educators, and all parties who are concerned about the future fate of the younger generation. Researchers conducted observations in class VIII of SMP Negeri 1 Rambipuji showing ethics in relationships that were a little low. This study aims to determine changes in ethics and the provision of group counseling on social ethics behavior of class VIII students at Rambipuji 1 Public Middle School. The type of research used is quantitative research. The procedure used is the provision of questionnaires, questionnaires given about the ethics of association and group counseling. Giving counseling groups can change ethical behavior in student association. Keywords : Social Ethics, Counseling Grup